Recent advances in fibrous catalysts for CO2 conversion: A short review - S. N., Miskan; R. S., Mohd Zaki; M. B., Bahari; H. D., Setiabudi; R., Jusoh (Elsevier Ltd, 2022)
In recent years, CO2 conversion reactions such as CO2 reforming of CH4 and CO2 methanation have devoted significant attention on account of their advantages in utilizing greenhouse gases (CO2 and CH4). The development of an excellent catalyst with great properties is a crucial strategy in the catalytic reaction, as it could enhance the efficiency of reaction. Additionally, the tunable characteristics of support materials may influence the distribution of active metal sites, strength of metal-supporting interactions, and amount of oxygen vacancies. To improve metal dispersion on a support, the production of support materials with fibrous morphology and dendrimeric structures is becoming an exciting approach. This short review highlighted recent developments in the preparation of fibrous catalysts and their relation with the physical and chemical properties of catalyst. This article also discussed the governing factor of fibrous morphology in CO2 conversions. Owing to the fascinating physicochemical properties of fibrous catalyst, further research is needed to explore its potential in various applications.